Climate Litigation and Justice in Africa - Bouwer, Kim; Etemire, Uzuazo; Field, Tracy-Lynn; Jegede, Ademola Oluborode (Bristol Studies in Law and Social Justice, 2024)
This volume brings together an international team of contributors to provide a much-needed examination of climate litigation in Africa. The book outlines how climate litigation in Africa is distinct as well as pinpointing where it connects with the global conversation. Chapters engage with crucial themes such as human rights approaches to climate governance, corporate liability and the role of gender in climate litigation.
Keywords: Africa; Climate adjudication; Climate governance; Climate justice; Climate litigation

The Concise Encyclopedia of Business Ethics - MacDonald, Chris; Marcoux, Alexei (Toronto Metropolitan University, 2023)
The authors’ aim in writing The Concise Encyclopedia of Business Ethics (CEBE) was to provide readers with a useful, concise overview of key issues in business ethics. Our aim is not to be exhaustive, but to provide key definitions, main areas of controversy, and pointers for further reading. It is hoped that it will provide a useful reference guide for students, as well as a starting point for scholars in adjacent fields. Our commitment to sticking to what we consider to be essential topics inevitably means that some readers will find that we have left out what they take to be important topics. For the most part, we stand by our editorial choices. However, as a digital document, it is possible that the CEBE will change and grow slightly over the coming years. Readers are free to provide feedback and suggestions by emailing the authors jointly at editors@bejr.org

Entrepreneurship in Africa - Akinyoade, Akinyinka; Dietz, Ton; Uche, Chibuike (African Dynamics, 2017)
Historically, entrepreneurs have always played a central role in the development of nation states. Aside from rentier states, which depend extensively on the availability of mineral resource rents, most economically prosperous nations in the world have strong, innovative and competitive business enterprises and entrepreneurs as the bedrock of their economic development and prosperity. It was arguably because of the above historical fact that the World Bank in 1989 declared that entrepreneurs will play a central role in transforming African economies. Chapters in this book contribute to our understanding of the theory, structure and practice of entrepreneurship in diverse African countries. Case studies examined include: African multinational banks and businesses, female entrepreneurs, culture and entrepreneurship, finance and entrepreneurship and SMEs.
Keywords: African Studies; Economic History; Economics & Political Science; History; Social Sciences; Sociology & Anthropology